Premature delivery impacts the concentration of plasminogen activators and a plasminogen activator inhibitor and the plasmin activity in human milk - Demers-Mathieu, Veronique; Underwood, Mark A.; Dallas, David C. (Frontiers in Pediatrics, 2022)
Background and Aims: Plasmin in human milk partially hydrolyzes milk proteins within the mammary gland and may enhance the hydrolysis of milk proteins within the infant’s stomach. This study examined the effects of extremely preterm (EP)-, very preterm (VP)- and term-delivery on plasmin activity and the concentrations of plasminogen activators (urokinase-type plasminogen activator (uPA) and tissue-type plasminogen activator (tPA)), plasminogen activator inhibitor type 1 (PAI-1) and the complexes of PAI-1/uPA and PAI-1/tPA in human milk. Methods: Human milk samples were collected from mothers who delivered extremely preterm infants (24–27 wk gestational age (GA), n = 20), very preterm infants (28–32 wk GA, n = 12) and term infants (38–39 wk GA, n = 8) during 2–72 days postnatally. Plasmin activity was determined using fluorometric substrate assay, whereas concentrations of uPA, tPA, PAI-1, the PAI-1/uPA complex and the PAI-1/tPA complex were quantified by ELISA. Results: Plasmin activity, uPA and tPA were detected in all human milk samples, PAI-1 and the PAI-1/uPA complex were present in 42.5% and 32.5% of milk samples, respectively, and the PAI-1/tPA complex was not detected. Plasmin activity was correlated negatively with postnatal age and postmenstrual age (PMA) in the VP group and positively with postnatal age in the term group. uPA and tPA concentrations decreased with increasing postnatal age in both EP and VP groups but did not correlate in the term group. uPA concentration was correlated positively with GA in the VP group and tended to be elevated with increasing GA in the combined 3 groups. In contrast, tPA concentrations were correlated negatively with GA and PMA in the combined 3 groups (P < 0.008) and with PMA in the EP and VP groups. PAI-1 concentration tended to be correlated positively with postnatal age in the combined 3 groups. No correlation was detected with the PAI-1/uPA complex. Conclusions: Premature delivery impacted the plasmin activity and the concentrations of uPA, tPA and PAI-1 in human milk. Whether these changes in milk plasminogen activators and inhibitors have a role in balancing the proteolytic digestion of premature infants remains to be investigated.